Characterization of microstructure evolution in β-γ TiAl alloy containing high content of Niobium using constitutive equation and power dissipation map. (5th October 2016) - Xin, Jingjing; Zhang, Laiqi; Ge, Gengwu; Lin, Junpin
Abstract: In order to study the hot deformation behavior and microstructure evolution of β-γ TiAl alloy containing high content of Nb, isothermal hot compression tests were conducted in the strain rate range of 0.001–1.0 s − 1 and temperature range of 1273–1473 K. The Arrhenius-type constitutive equation was successfully established for expressing the non-linear relation among true stress, strain, strain rate and deformation temperature. The average absolute relative error and correlation coefficient are 6.009% and 0.9961, respectively, which reflects good predicted accuracy of developed constitutive equation. Conventional and 3D power dissipation maps based on the developed constitutive equations and dynamic material model were successfully established. Efficiency of power dissipation increases with higher deformation temperature, lower strain rate and higher strain, which indicates that more power is dissipated through changing microstructure. These deformed specimens with equal efficiency of power dissipation exhibit similar microstructures during hot deformation. The content of dynamic recrystallization (DRX) grains increases with the increase of efficiency of power dissipation ( η ). The microstructures with η  ≥ 0.55 mainly consist of equiaxed DRX grains, corresponding to the temperature range of 1273–1473 K and the strain rate range of 0.001–0.01 s − 1 at the strain of 0.5, which could be the optimum hot working window of alloy. Graphical abstract: Highlights: β-γ TiAl alloys containing high content of Nb have excellent hot-working characteristic. The developed Arrhenius-type constitutive equation reflects the good predicted accuracy. 3D power dissipation maps based on Arrhenius-type constitutive equations and dynamic material model were established. The developed power dissipation maps can predict and characterize microstructure evolution during hot deformation.